A constructivist paradigm in addressing psychosocial issues in genetic counseling - Angeles, Liezel B.; Ho, Leticia Penano; Rayco, Domingo R.; De Guzman, Ligaya S.; Cajilig, Norma G.; De La Paz, Eva Maria C. (Quezon City College of Education, University of the Philippines Diliman, 2015)
Genetic counseling refers to the process of helping people understand and adapt to the medical, psychosocial and familial implications of genetic disease. The principal aim of this study is to develop a theoretical framework to describe the psychosocial orientation of genetic counseling. The study utilized a grounded theory approach in examining the experiences and concerns of the geneticists, the patients and their families; the genetic counseling goals, processes and outcomes; and other health professionals’ views. The data for this research were obtained by interviewing 38 primary caregivers, 5 geneticists, and 7 health professionals. The study was limited to patients who screened positive of newborn screening disorders on congenital hypothyroidism, congenital adrenal hyperplasia, phenylketonuria, galactosemia, and glucose-6-phospate dehydrogenase deficiency. This study showed that the patients’ parents had basic information about the disorder but were unaware of genetic counseling concepts. Geneticists were focused on formal, holistic and patient-centered education while the parents were more concerned with functional daily management. Although management of the disorder is not part of genetic counseling, the parents faced multifaceted psychosocial issues that arose from informational, management and relational factors. Families dealt with the genetic disorder through graded adaptation. The formation of worldviews or resolution of dissonance of parents contributed to transition to more adaptive grade. However, some families were found straddling between graded because they were confronting residual issues of the initial grade. The researcher recommends a constructivist paradigm in genetic counseling based on the examination of familial processes and recognition of the family’s adjustment through graded adaptation.
Thesis
Includes bibliographical references (pages 444-455)
Keywords: Genetic counseling -- Social aspects -- Philippines -- Manila; Genetic counseling; Newborn infants -- Diseases -- Diagnosis; Genetic disorders; Genetic diseases, Inborn; Newborn infants -- Philippines -- Manila